2013
DOI: 10.1016/j.celrep.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

SorLA Controls Neurotrophic Activity by Sorting of GDNF and Its Receptors GFRα1 and RET

Abstract: Glial cell-line-derived neurotrophic factor (GDNF) is a potent neurotrophic factor that has reached clinical trials for Parkinson's disease. GDNF binds to its coreceptor GFRα1 and signals through the transmembrane receptor tyrosine kinase RET, or RET independently through NCAM or syndecan-3. Whereas the GDNF signaling cascades are well described, cellular turnover and trafficking of GDNF and its receptors remain poorly characterized. Here, we find that SorLA acts as sorting receptor for the GDNF/GFRα1 complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 54 publications
2
55
0
1
Order By: Relevance
“…This is most likely due to the sequence divergence and presumable structural divergence seen from the poorly conserved sequence identity (Tables 2 and 3) and from the alignments (Fig 8). There might not be a conserved RET/GFRα/GDNF signaling system in fruit fly and perhaps dRET might be constitutively held inactive by dGFRLs, as a part of a sorting receptor protein complex as has been suggested for other GFRα molecules [38]. These results question the role of dRET with a functional active tyrosine kinase domain as shown by Abrescia et al .…”
Section: Discussionmentioning
confidence: 97%
“…This is most likely due to the sequence divergence and presumable structural divergence seen from the poorly conserved sequence identity (Tables 2 and 3) and from the alignments (Fig 8). There might not be a conserved RET/GFRα/GDNF signaling system in fruit fly and perhaps dRET might be constitutively held inactive by dGFRLs, as a part of a sorting receptor protein complex as has been suggested for other GFRα molecules [38]. These results question the role of dRET with a functional active tyrosine kinase domain as shown by Abrescia et al .…”
Section: Discussionmentioning
confidence: 97%
“…SORLA interacts with GDNF to increase its regulated secretion from cells [47]. In addition, SORLA interacts with GFRα1, the co-receptor for GDNF [48]. SORLA facilitates internalization of GFRα1/GDNF complexes from the plasma membrane, resulting in lysosomal catabolism of GDNF but cell surface recycling of GFRα1.…”
Section: Sorla In Neurotrophin Signalingmentioning
confidence: 99%
“…SORLA facilitates internalization of GFRα1/GDNF complexes from the plasma membrane, resulting in lysosomal catabolism of GDNF but cell surface recycling of GFRα1. This sorting route provides an efficient pathway for clearance of GDNF from the extracellular space and counteracts consequences of excessive GDNF signaling, such as hyperactivity and reduced anxiety (as seen in mice lacking SORLA) [48]. Finally, SORLA also impacts signaling through a heterodimeric neurotrophic cytokine called cardiotrophin-like cytokine:cytokine-like factor 1 (CLC:CLF-1) [49].…”
Section: Sorla In Neurotrophin Signalingmentioning
confidence: 99%
“…Additionally, single-site and haplotype association of SORL1 with risk of amnestic mild cognitive impairment (aMCI), a common precursor to AD, has been reported in the Han Chinese [88]. Glerup et al [89] have demonstrated SORL1 as an endocytic modulator of glial-derived neurotrophic factor (GDNF) and its related receptor, GFRα1.…”
Section: Identification Of Load Genes By Genome-wide Association Studiesmentioning
confidence: 99%